Unearthing the behavioural factors influencing commodity futures contracts adoption in agriculture - A systematic literature review - Wever, Hendrik; Michels, Marius; Musshoff, Oliver (Australian Journal of Agricultural and Resource Economics, 2024)
Farmers' adoption of commodity futures and options contracts (CFCs) in agriculture shows substantial variation across different regions. Sociodemographic and farm characteristics fail to fully account for these observed differences. Hence, research focuss
Keywords: Commodity Futures Contracts; Futures and Options; Price Hedging; PRISMA; Systematic Literature Review; Behavioural Factors